Female managers and their wages in Central Europe - Štepán Jurajda; Teodora Paligorova (Institute for the Study of Labor (IZA), 2006)
This paper examines the gender gaps in employment and wages among top- and lower-level managerial employees in a recent sample of Czech firms. Unlike the existing analyses of managerial gender pay gaps, we acknowledge the adverse consequences of the low and uneven representation of women for the Oaxaca-Blinder decomposition and offer an alternative set of results based on a matching procedure. Only 7% of top-level Czech managers are women and their wages are about 20 percent lower even when compared only to their comparable male colleagues.
Keywords: 330